2001
DOI: 10.1007/s002130000575
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine in the treatment of Huntington's disease

Abstract: Firm conclusions to explain these results cannot be drawn. However, a hypothetical involvement of the serotonergic system, suggested by the excess of OCD in the pedigree, seems supported by the response of these two individuals to fluoxetine. It may be worth further exploring the value of the psychiatric picture in selecting the appropriate treatment for at least some cases of HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…From these results, we conclude that antidepressants with a more specific action on serotonin and norephineprine may provide greater protection against 3-NP neurotoxicity. Some clinical studies have also indicated the therapeutic potential of these antidepressants in HD patients (Shoulson, 1981;De Marchi et al, 2001). Jin et al (2009) reported that fluoxetine suppressed kainic acid-induced neurotoxicity in the hippocampus).…”
Section: Discussionmentioning
confidence: 97%
“…From these results, we conclude that antidepressants with a more specific action on serotonin and norephineprine may provide greater protection against 3-NP neurotoxicity. Some clinical studies have also indicated the therapeutic potential of these antidepressants in HD patients (Shoulson, 1981;De Marchi et al, 2001). Jin et al (2009) reported that fluoxetine suppressed kainic acid-induced neurotoxicity in the hippocampus).…”
Section: Discussionmentioning
confidence: 97%
“…Olanzapine [80•] Open trial, 11 Improvement in five patients on "overall behavior"; irritability improved, aggression unchanged; depression, anxiety, and obsessions also improved in some patients Olanzapine [81] Case report, 1 Improvement in aggression and irritability (symptoms disappeared after 5 months of olanzapine treatment) Fluoxetine [82] Case report, 1 with irritability and agression (second patient also treated with fluoxetine for movements only) Improvement in irritability and aggression; authors suggest that this may be due to treatment of underlying obsessive-compulsive disorder Olanzapine and divalproex [83] Case reports, 2 Improvement (psychotic symptoms with aggression) Buspirone [84] Case report, 1 Improvement Sertraline [85] Case reports, 2 Improvement Clozapine [78] Retrospective case reviews, 2 with aggression, 2 with delusions (eight patients total, four tried clozapine for chorea only) Improvement in aggression and delusions; considerable sedation in seven of eight patients…”
Section: Comments and Outcome On Target Symptomsmentioning
confidence: 98%
“…A report of two patients with genetically confirmed HD from the same extended pedigree were administered fluoxetine 20 mg/day for disabling obsessive-compulsive disorder. 98 Both patients had a sustained improvement in UHDRS chorea score (by 8 and 5 points), with prompt worsening on attempts to discontinue the drug. However, in the case of a 46-year-old man with genetically confirmed HD who was treated with fluoxetine 20 mg daily for new-onset disabling obsessive-compulsive disorder, chorea worsened within several days after initiating the treatment, although his decline was not quantified.…”
Section: Antidepressantsmentioning
confidence: 91%